Effect of Kitolod (Hippobroma longiflora L.G. Don) Extract on Apoptosis through Bcl-2 and Caspase-3 Expression in Wistar Rats (Rattus norvegicus) Induced by Benzo[a]pyrene - Ana Bina Sari; Eman Sutrisna; Daniel Joko Wahyono (Indonesian Socety of Obstetrics and Gynecology, 2026)
ABSTRACT Objective: This study aimed to evaluate the effect of ethanol extract of H. longiflora leaves on apoptosis regulation through Bcl-2 and Caspase-3 expression in BaP-induced Wistar rats (Rattus norvegicus). Methods: An experimental study with a post-test only control group design was conducted. Twenty-five female Wistar rats were randomly allocated into five groups: healthy control, negative control (BaP only), and three groups receiving kitolod extract at 100, 200, or 300 mg/kg BW. BaP administration was followed, one hour later, by co-treatment with the extract for 30 consecutive days. Cervical tissues were analyzed immunohistochemically for Bcl-2 and Caspase-3 expression. Results: Kitolod extract significantly reduced Bcl-2 expression compared with the negative control (p < 0.05) and increased Caspase-3 expression, with the strongest effect observed at 300 mg/kg BW. The healthy control group exhibited the lowest expression levels, while the negative control group showed the highest, demonstrating a consistent dose-response relationship. Conclusion: Ethanol extract of H. longiflora leaves suppressed Bcl-2 and enhanced Caspase-3 expression, thereby promoting activation of the intrinsic apoptotic pathway. Keywords: Hippobroma longiflora, benzo[a]pyrene, Bcl-2, Caspase-3, apoptosis, cervical cancer